Emotional Loneliness, Suicidal Ideation, and Alexithymia in Adolescents Who Commit Child-to-Parent Violence - Suárez-Relinque, Cristian (Journal of interpersonal violence, 2023)
The objective of this research was to explore the relationship between involvement in child-to-parent violence (CPV) and the development of emotional loneliness, suicidal ideation, and alexithymia based on sex; 1,928 adolescents of both sexes participated (50.5% males and 49.5% females), aged between 12 and 18 years (M = 14. 67, SD = 1.77), enrolled in four educational centers in Spain. A multivariate analysis of variance (3 × 2 MANOVA) was applied using sex and CPV levels as independent variables. Univariate analyses were carried out to explore the significant relationships detected. Results showed that the adolescents with higher CPV scored higher in emotional loneliness, suicidal ideation, and alexithymia. Girls showed a greater prevalence of CPV at the medium and high levels. An interaction of sex and CPV with alexithymia was detected. Girls with high and moderate values of CPV presented a higher level of alexithymia. These results provide novel information in the field of CPV. Previous research has placed the main focus of analysis on the adolescents’ behavior problems and not so much on their perceptions of personal adjustment and their emotional experiences. The information presented in this study contributes to achieve a more precise definition of the profile of adolescent who assault their parents for better prevention of CPV.